Legal Relationship Between the Parties with a Construction Working Contract in The Indonesian Contract Legal System - Manurung, Edision Hatoguan (Future Science, 2021)
The purpose of this study is to analyze the legal relationship between the parties through the construction work contract of the Indonesian contract law system. The method used is normative juridical. The results of the research regarding unilateral termination can only be carried out by buyers who are considered too unilateral. Because in fact, there are still several obstacles, those are service users as buyers violating the contract and performance in the form of late payments. However, in this case, if an agreement to terminate the contract is not obtained from the service user, then the contractor cannot terminate the contract. Therefore, even though it is regulated in the Civil Code that unilateral termination of employment can only be carried out by the contractor, it is necessary to evaluate the unilateral termination arrangement in the existing building contract.